2021
DOI: 10.1155/2021/8817502
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs11780592 Polymorphism in the Human Soluble Epoxide Hydrolase Gene (EPHX2) with Oxidized LDL and Mortality in Patients with Diabetic Chronic Kidney Disease

Abstract: Soluble epoxide hydrolase 2 (EPHX2) is an enzyme promoting increased cellular apoptosis through induction of oxidative stress (OS) and inflammation. The EPHX2 gene which encodes soluble EPHX2 might be implicated in the pathogenesis and development of OS and atherosclerosis. We aimed to assess the possible association between two functional polymorphisms of the EPHX2 gene (rs2741335 and rs11780592) with oxidized LDL (ox-LDL), carotid atherosclerosis, mortality, and cardiovascular (CV) disease in 118 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In T2DM patients, both ADMA and limited nitric oxide bioavailability, independently from each other, predict micro and macrovascular complications, including onset of DKD [ 23 ]. Moreover, the rs11780592 polymorphism of the soluble epoxide hydrolase 2 (EPHX2), an enzyme triggering cellular apoptosis through induction of OS and inflammation, was associated with ox-LDL, albuminuria, and mortality in a cohort of DKD patients [ 24 ]. But even locally, experimental data suggest that ox-LDL might play a key role in the development of glomerulosclerosis in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…In T2DM patients, both ADMA and limited nitric oxide bioavailability, independently from each other, predict micro and macrovascular complications, including onset of DKD [ 23 ]. Moreover, the rs11780592 polymorphism of the soluble epoxide hydrolase 2 (EPHX2), an enzyme triggering cellular apoptosis through induction of OS and inflammation, was associated with ox-LDL, albuminuria, and mortality in a cohort of DKD patients [ 24 ]. But even locally, experimental data suggest that ox-LDL might play a key role in the development of glomerulosclerosis in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…The EPHX2 gene encodes soluble epoxide hydrolase (sEH), a bifunctional enzyme of the epoxide hydrolase family, an enzyme that promotes increased apoptosis by inducing oxidative stress and inflammation [ 86 ]. Thomassen et al found that sEH degrades biologically active epoxy fatty acids derived from arachidonic acid through the metabolism of P450 cytochromes (CYP) in the arachidonic acid pathway [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rs11780592 polymorphism of Ephx2 (the gene that encodes sEH) has been associated with increased oxidized LDL, carotid intima-media thickness, and mortality in individuals with diabetic chronic kidney disease [ 47 ], suggesting that genetic variants may influence endothelial dysfunction and progression of renal damage in T2DM.…”
Section: Oxylipins and Complications Of Diabetesmentioning
confidence: 99%